Analisis Potensi Pengembangan Sapi Potong di Kabupaten Bima Nusa Tenggara Barat - Mursidin, Mursidin; Jufrin, Jufrin; Susanti, Handayani Indah; Irmawaty, Irmawaty; Astati, Astati; Ananda, Suci (Anoa: Journal of Animal Husbandry, 2025)
The beef cattle business in Bima Regency has a strong enough base to support the potential of livestock farming. This study aims to analyze the potential for beef cattle development in Bima Regency, West Nusa Tenggara. The method used is a survey method. Data collection was carried out using the Judgment Sampling method. The sampling technique was based on relevant information available from the Central Statistics Agency (BPS) of West Nusa Tenggara Province, the BPS of Bima Regency, and the Livestock and Animal Health Service of Bima Regency in 2022. The variable analyzed in this study is the Beef Cattle Population. All data obtained were analyzed using three data analysis methods, including Location Quotient (LQ) analysis, Growth Analysis, and Share Analysis. Based on the analysis results, this study shows that the potential for beef cattle development in Bima Regency using the Location Quotient (LQ) formula indicates a basic sector with a result of 1.02, which means that beef cattle farming in Bima Regency can be developed. Bima Regency's growth value indicates increased productivity growth for exports, reaching 3.84% in 2021 and 13.78% in 2022. The value obtained from the calculation using the Share formula is 20.27%, which means (+), and it can be concluded that Bima Regency makes a significant contribution to exports.